Synthesis, characterization, and electrical properties of metal complexes of 2-pyridinecarbaldehyde thiosemicarbazone - Yakuphanoğlu, Fahrettin; Balaban, A; Dagdelen, F; Aydogdu, Y; Sekerci, M; Erk, B (Marcel Dekker Inc, 2002)
The synthesis, characterization, physico-chemical and electrical properties of complexes of pyridine-2-carbaldehyde thiosemicarbazone (PTSC) with transition element cations are reported. The complexes [Fe(PTSC)(2)Cl-2]Cl and [Ni(PTSC)(2)-(H2O)(2)]Cl-2 were prepared. Molecular structures of these complexes were identified by-using elemental analyses, FT-IR, UV-VIS, thermogravimetric and molar conductivity techniques. The structure, along with other physico-chemical studies, established that the complexes of PTSC were low-spin. The spectroscopic study of the compounds showed that the transition metal complexes had octahedral geometry. A spectrophotometric determination of nickel(II) with pyridine-2-carbaldehde thiosemicarbazone in methyl alcohol solution is proposed and the stability constants of the nickel(II) complex were determined by the Job method. The electrical conductivity of the compounds increases with elevated temperature. Their conductivities follows the order Ni > Fe. The calculated values of the activation energy of mobility, Emu, suggests that conduction in the studied complexes takes place by a hopping mechanism, where one electron hops from one molecule to another.
Keywords: Schiff-Base Complexes; 2-Acetylpyridine; Iron(Iii); Crystal